Globalization: Its Impact on and Challenges to Education in the Muslim World (American Journal of Islam and Society, 2010)
More than thirty years ago, the first World Conference on Muslim Educationembarked upon the “Islamization of Knowledge,” a process articulated andexpounded upon by the late Ismail Raji al-Faruqi (Temple University) andNaguib al-Attas, retired (ISTAC, Malaysia). The organizers of this conference,the seventh in this series, hoped to continue in this spirit by aiming “tobe as dynamic and as influential as its predecessors” and to develop themesdiscussed in earlier conferences by locating them within “the current globalizedatmosphere.” Moreover, it “expected to usher in a new era of Muslimeducation which will counteract the negative effects of globalization…”The organizers listed three special themes: “Curriculum for MuslimEducation,” “Making Basic Teachings of Islam Relevant,” and “Religionand Youth” and twelve subthemes, among them “Integration of Knowledge,”“Madrasah Education,” “Quality of Muslim Education,” “Non-Muslim Perspectives on Muslim Education,” and “Principles of Critical andCreative Thinking in Muslim Education.” They also invited particular individualsto present papers, such as Wahbah Zuhayli (dean, Faculty of IslamicLaw, University of Damascus [Syria]), Anis Ahmad (Riphah InternationalUniversity [Pakistan]; editor, The Quarterly Journal of the West & Islam),and Alparslan Acikgenc (Fatih University [Turkey]). Since the conferencecovered a variety of keynote speeches, presentations by well-known Malaysianscholars such as Osman Bakar (International Institute of AdvancedIslamic Studies, Malaysia) and Kamal Hassan (International Islamic UniversityMalaysia) and parallel sessions, I will comment briefly on the sessionsand more extensively on some of the keynote speeches that set the tonefor the discussions at the conference ...